An Analysis of Instagram as a Government Public Information Platform Through Piere Levy's Theory - Nuriyati Samatan; Robingah Robingah; Jun Firmansyah; R.Z. Rasyid (Siber Nusantara of Community Service Review, 2025)
This study analyzes Instagram social media as a public information platform for the government using Pierre Levy's theory. The study was conducted based on the Instagram account of the Depok City Government @pemkotdepok. The analysis used Pierre Levy's New Media Theory, with the following assumptions: utilization, social media, communication, and information. The study used qualitative methods, with a constructivist paradigm, research study type, through observation, interviews, and documentation. The research and observation were conducted over a period of 4 months to observe the activities of the Instagram account, interview the administrators and the Depok City Government, and documentation throughout the research. The results of the study showed that the Depok City Government utilizes Instagram as a medium for disseminating information by utilizing Instagram features. The study found that the @pemkotdepok Instagram account is a transparent, innovative, and informative public information platform that attracts Instagram users to the information provided by the Depok City Government and serves as an accurate source of information for various policies and public information. Analysis using Pierre Levy's theory found that the assumptions of Collective Intelligence, Virtual and Actual, New Media as a social environment, User Interactivity and Engagement, as well as cultural and cognitive changes.